Analisis dan Perkuatan Kolom Baja Struktural Akibat Beban Gempa Menggunakan HBeam - Silvi, Ni Putu; Laintarawan, I Putu (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
Evaluation or study of existing building structures must consider the strength and stiffness of structural components due to gravity loads and earthquake loads. The strengthening to the existing Hbeam column structure is to add steel plates to the existing Hbeam column. This method is a way to improve structural performance due to earthquake loads in terms of ease of implementation, time and cost when compared to replacing or adding new structural components. The purpose of this study was to analyze the strengthening of Hbeam column steel plate due to seismic loads. Parameters analyzed were vibration period, lateral displacement and internal forces due to earthquake loads. This research is a quantitative analytical research, where the geometry data of the 3D frame portal structure is determined independently, while the material and loading data are based on (SNI 1727:2013) and (SNI 1729:2019). The 3D frame portal is modeled and analyzed using finite element based software, ETABS software. The results of the analysis show that the strengthening of the Hbeam column by adding a steel plate to the existing Hbeam column which is installed horizontally in the middle of the cross section with dimensions of 15 mm thick and 145 mm long (18.59% of the cross-sectional area of the Hbeam column) increases the stiffness of the structure by 12.01% and 14.2% respectively - for vibration period and lateral drift, respectively. The lateral displacement is smaller than the allowable lateral displacement with a drift ratio of less than 130%, so the structure does not experience a soft story. The average maximum internal forces (moment, shear and axial force) due to the earthquake load of the column structure with reinforcement increased by 12.50%, 9.68% and 14.01% respectively compared to the structure without strengthening along with the addition of dimensions to the existing Hbeam column.